El Impacto de la Globalización sobre las Estrategias de Mercadotecnia - Alfaro-Roman, Alexander; Hidalgo-Mesen, Alexander; Zeledón-Lostalo, Eugenia (Instituto Tecnológico de Costa Rica, 2001)
The following investigation objective is to explain the transformation that the marketing strategy formulation in some big national and foreign businesses in Costa Rica, regarding the Globalization process has done. The investigation was made as a request to obtain a Licentiate in Marketing at the Instituto Tecnológico de Costa Rica. The main teoric concepts served as a fundaments and orientation for the development, we present relevant themes like globalization, globalize strategies and global market, even all themes related to develop and global marketing application. At the same time, to achieve the objectives, the research team did a breakdown of the study under three different points of view: a) Foreign companies that under the new Globalization Era have come to compete in the Central American market. b) Domestic companies that have faced the arrival of foreign competition. c) Domestic companies that in addition of competing with foreign industries, have looked for growing opportunities in other markets, all under the Globalization environment. In each one of these points of view, three companies were analyzed. These companies were chosen under the scrutiny and convenience of the research team. To do this and structured and individual interviewed was designed and applied to the executives or directors in charge of the marketing area of each one of these organizations. Concluded the stage of information was proceeded to the elaboration of comparative squares between the studied companies, assembling them according to the focus under the who they were analyzed, detailing the principal change applied in the different variables that conform the marketing mix, like the description of the several strategies for those in each womb that to organization level, they have opted these companies in order to maintain their competition level and growth. iv The main topics founded on each scope were: Scope a) Scope b) Scope c)  Production concentration in strategic points in order to get scale economies.  High investments in research and development.  Better distribution coverage.  Constant innovation in their products.  Products standardization.  Usage of latest technology.  Administrative functions concentration.  Administrative functions concentration.  Diversified line of goods  Goods exportation to Central America.  Formal strategic alliances on distribution.  Other companies acquisition.  Maquila production to other brands, inclusive contenders.  Advertisement investment looking forward new point of sales.  ISO quality certification.  Innovative products line.  New factories installation in Costa Rica and Central America.  Corporate image exportation.  Price strategy varies according to industry.  Direct delivery of goods. To finalize, analyzing the results of this investigation as a whole and going back to its original objective, it has been concluded that, generally speaking, the modern businessman's philosophy, characterized by being submerged in an globalized marked of intense activity, has had to transform itself, to understand that it is not standing alone in the market, that all around him there are an immense range of solutions offered by the competition, which is eager to satisfy the needs of its market with alternatives and services of great innovation and focused totally on the client. In this sense, today’s entrepreneur needs to broaden his/her way of thinking and look for options, through the various forms of alliance and other corporate strategies in order to get to the market faster than the others. This can be carried out with innovative products or services that at the same time are efficient and posses an excellent quality. Moreover, a series of additional services that give him the value added necessary to see the difference clearly before his/her competitors, provides the desired positioning attained with success.
Proyecto de Graduación (Licenciatura en Mercadeo). Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2001.
Keywords: Canales de distribución; Ambiente político; Ambiente cultural; Estrategias; Corporación